Meningkatkan Keputusan Pembelian Melalui Peran Mediasi Citra Merek Pada Warunk Upnormal Cibinong - Evi Elyanti Situmorang; Parlagutan Silitonga (LPPM Universitas Asa Indonesia, 2022)
This study aims to prove the influence of product quality, and atmosphere on purchasing decisions through brand image. The population in this study were customers who bought at Warunk Upnormal Cibinong. The sampling technique used accidental sampling of 132 respondents. The data collection method uses questionnaires that are distributed to respondents. The data analysis used is a test of validity and reliability, while for hypothesis testing includes path analysis, evaluation of measurement and structural models. The results of this study show that the value of each variable either directly or indirectly has a positive and significant influence. So it can be concluded that the implications of this study reveal product quality and atmosphere are important elements of the brand image and purchasing decisions to continue to be improved.